Risk Factors Associated With Incomplete Colonoscopy Based on the Analysis of Computed Tomographic Colonography Findings. Issue 5 (September 2018) - Lee, Eun Sun; Kim, Byung Chang; Hur, Bo Yun; Kim, Min Ju; Park, Hyun Jeong; Park, Sung Bin; Lee, Jong Beum; Sohn, Dae Kyung; Han, Kyung Su; Hong, Chang Won
Abstract : Objective: This study aimed to identify the computed tomographic colonography (CTC) findings of incomplete colonoscopy compared with those of complete colonoscopy. Methods: The clinical data and CTC imaging data from January 2004 to December 2012 were retrospectively obtained at 2 different institutions and reviewed by the central review system. A total of 71 patients who underwent both videocolonoscopy and CTC were included in this study. The CTC findings and clinical data were evaluated for the completeness of colonoscopy. Results: In the CTC analysis, differences in total colon length, abdominal circumference, and sigmoid colon diameter were statistically significant between both groups ( P < 0.05). Body mass index (BMI) and height were identified as significant clinical factors influencing the completeness of colonoscopy. In multiple logistic regression tests, only BMI and sigmoid colon diameter were independent factors ( P < 0.05). Conclusions: High BMI larger diameter of sigmoid colon was associated with incomplete colonoscopy based on CTC.